The training process and Accelerating Capabiltiy Development (ACD) in closing the gaps and increase competency among staff: a study on Petronas Carigali Sdn Bhd, Sabah operation - Jumat, Mohd Azrul (2009)
This report investigates the effectiveness and efficiency of the training programs at PCSB/ SBO. This research wants to find out whether the training process and ACD program are useful in increasing staff’s competency. The training program is important to develop and explore the capabilities of the staff and to "value- added” the product to be different from other competitors. Without it, the organization will not be able to catch or learn new skills and knowledge especially in the operating management. The purpose of conducting this survey is tried to analyze the areas that the company should focus more in providing their training programs. We sought opinions and recommendations based on the findings on how to improve the levels of training programs. A total of 80 respondents from selected four (4) training programs conducted in the 2nd quarter of the year of 2009 to be analyzed their effectiveness. Using quantitative analysis, the data were computed by using the specific calculation formulas and converted into chart and percentage. From the information obtained, the main finding is that the training programs conducted were excellent. From the findings, we can conclude that the organization were concern with the training programs and focus on the better results of the training programs. However, there is some of the inefficient of the training program. By conducting this study, I hope that the results and some of the recommendations can help the PCSB/ SBO to improve its training program from planning until the evaluation stage in the future.